Lateral nasal wall extension of the nasoseptal flap for skull‐base and medial orbital wall defects. Issue 9 (7th June 2019) - McCormick, Justin; Allen, Mark; Kain, Joshua J.; Pena‐Garcia, Jaime A; Cho, Do‐Yeon; Riley, Kristen O.; Woodworth, Bradford A.
Abstract : Background: Sinonasal and skull‐base tumors that previously required open resection can often be completely resected via an endonasal approach. The nasoseptal flap (NSF) is the workhorse vascularized tissue flap for the endoscopic reconstruction of large skull‐base defects from tumor resections. The objective of the current article is to describe a novel modification of the NSF for simultaneous reconstruction of skull‐base and medial orbital wall defects. Methods: An extension of the standard NSF to include mucosa of the lateral nasal wall was developed for closure of simultaneous skull‐base and medial orbital wall defects. Outcomes including successful cerebrospinal fluid (CSF) leak closure, orbital edema, and postoperative cosmesis are reported. Eyelid edema was characterized according to the Surgeon Periorbital Rating of Edema and Ecchymosis (SPREE) scale. Results: Three patients underwent reconstruction using the modified NSF (average age 75 years). The average defect size of the skull base was 3.6 ± 0.1 cm by 2.3 ± 0.2 cm. The average defect size of the medial orbit was 2.7 ± 0.1 cm by 2.6 ± 0.1 cm. All defects were successfully covered intraoperatively using the lateral nasal wall extension of the NSF. Two patients developed mild eyelid edema, whereas 1 individual had no noticeable swelling (SPREE classification 2, 2, and 1). All patients were successfully sealed at last clinical follow up (average 28 weeks). Conclusion: The modification of the NSF described here provides excellent coverage for reconstruction of large anterior skull‐base defects and simultaneous medial orbital wall defects.